A novel SCN9A splicing mutation in a compound heterozygous girl with congenital insensitivity to pain, hyposmia and hypogeusia. Issue 3 (23rd July 2018) - Marchi, Margherita; Provitera, Vincenzo; Nolano, Maria; Romano, Marcello; Maccora, Simona; D'Amato, Ilaria; Salvi, Erika; Gerrits, Monique; Santoro, Lucio; Lauria, Giuseppe
Abstract : Congenital insensitivity to pain (CIP) is a rare autosomal recessive disorder presenting with a spectrum of clinical features caused by mutations in different genes. A 10‐year‐old girl with CIP, hyposmia and hypogeusia, and her unaffected twin and parents underwent next generation sequencing of SCN9A exons and flanking splice sites. Transcript analysis from whole blood successfully assayed the effect of the mutation on the mRNA splicing by polymerase chain reaction amplification on cDNA and Sanger sequencing. We identified the novel splicing variant c.1108‐2A>G compound with the p.Arg896Gln (c.2687G>A) missense mutation previously described in a homozygous patient. The new intronic variant was predicted to induce exon 10 skipping. Conversely, SCN9A mRNA assay demonstrated its partial deletion with a loss of 46 nucleotides causing a premature stop codon in position p.Gln369 (NP_002968). Genetic analysis showed that the two variants were biallelic, being the mother and brother heterozygous carriers of the missense mutation, and the father heterozygous for the splicing mutation. Skin biopsy showed lack of Meissner's corpuscles, loss of epidermal nociceptors and normal autonomic organ innervation. We report a novel splicing mutation and provide clues on its pathogenic effect, broadening the spectrum of genotypes and phenotypes associated to CIP.